The necroptosis-related lncRNA ENSG00000253385.1 promotes the progression of esophageal squamous cell carcinoma by targeting the miR-16-2-3p/VDAC1 axis - Xiaoyang Duan; Jian Shi; Ran Hou; Yajie Huang; Chunyan Wang; Huazhen Du (Scientific Reports)
Abstract Esophageal squamous cell carcinoma (ESCC) is one of the most common digestive malignancies. Our previous studies revealed necroptosis-related lncRNA ENSG00000253385.1 was an independent prognostic factor for ESCC. However, the specific regulatory mechanisms are unknown. This study aimed to investigate the expression of the lncRNA ENSG00000253385.1 in ESCC tissues and its relationship with clinicopathological features and patient prognosis, and to explore its potential regulatory mechanism in ESCC cells. We detected the location of the lncRNA ENSG00000253385.1 in ESCC cells by fluorescence in situ hybridization (FISH). FISH and quantitative real-time polymerase chain reaction (qRT‒PCR) were used to detect gene expression in ESCC tissues and cells. Cell proliferation, migration and apoptosis were evaluated by CCK-8 assay, wound healing, transwell cell migration, invasion and flow cytometry assay. The levels of necroptosis-related protein were detected by western blot. The binding sites between miR-16-2-3p and lncRNA ENSG00000253385.1 or voltage-dependent anion channel 1 (VDAC1) were predicted by bioinformatics database and confirmed by dual luciferase reporter gene assay. Results revealed that the lncRNA ENSG00000253385.1 expression was higher in ESCC tissues than in the adjacent tissues. High lncRNA ENSG00000253385.1 expression, positive lymph node metastasis and clinical stage III were associated with poor overall survival (OS) in patients with ESCC, and were independent risk factors for prognosis of patients with ESCC. The lncRNA ENSG00000253385.1 was located in the cytoplasm. MiR-16-2-3p had a direct targeting regulatory relation ship with lncRNA ENSG00000253385.1 and VDAC1. MiR-16-2-3p inhibitor promoted proliferation, migration and invasion, and inhibited apoptosis of ESCC cells. Knockdown of the lncRNA ENSG00000253385.1 could inhibit the proliferation, migration and invasion, promote the apoptosis, and result in increases in the necroptosis-related proteins p-receptor-interacting protein kinase 3 (RIPK3)/RIPK3 and p-mixed lineaae kinase domain-like protein (MLKL)/MLKL and a decrease in the VDAC1 protein levels in ESCC cells, whereas miR-16-2-3p inhibition rescued these effects. Therefore, The lncRNA ENSG00000253385.1/ miR-16-2-3p/VDAC1 axis may be considered as a potential predictive biomarker and target for ESCC.